A battery integrated multiple input DC-DC boost converter - Azuka Affam; Yonis M. Yonis Buswig; Al-Khalid Hj Othman; Norhuzaimin Julai; Hani Albalawi (Bulletin of Electrical Engineering and Informatics, 2023)
In this paper, the proposed single boost converter aims to harness more than one renewable energy (RE) input source and achieve a high voltage gain. The interleaved technique combined with voltage multiplier (VM) cells, reduced inductor current and attained high voltage transfer ratio. The boost converter possesses two unidirectional input ports and a bidirectional input port that is connected to a battery storage. The duty ratios of the power and interleaving switches are used to regulate the output voltage of the proposed converter. Three operation modes are identified, and steady state analyses of the converter are presented and discussed. The converter can store excess energy in the battery during periods of abundance and deliver power to the loads when the RE sources are low or unavailable. In addition, the output voltage is higher than that of the conventional boost converter. The converter delivered 278 V from 12 V and 24 V dual input sources. The converter operation is simulated and verified using MATLAB/Simulink.